The radical humanism of Erich Fromm - Durkin, Kieran; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book argues that Fromm is a vital and largely overlooked contribution to twentieth-century intellectual history, and one who offers a refreshingly reconfigured form of humanism that is capable of reintegrating explicitly humanist analytical categories and schemas back into social theoretical (and scientific) considerations.
Keywords: Science